2022
DOI: 10.1097/rhu.0000000000001815
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic Spondylitis: A Disease Manifestation in Debate

Abstract: With the advent of classification criteria for psoriatic arthritis (PsA) and axial spondyloarthritis (axSpA), patients with axial manifestations associated with psoriasis, initially described in the l950s as a specific entity termed psoriatic spondylitis (PS), are now categorized within PsA, ankylosing spondylitis (AS), and axSpA. Thus, different terms are used to describe axial disease in patients with PsA including PS, axial psoriatic arthritis (axPsA), and psoriatic spondyloarthritis. Patients with PS may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Up to 75% of axial PsA patients with longstanding disease have cervical spine damage involving C1-C2, where odontoid erosions and atlantoaxial instability can be found, leading to further complications, such as spinal cord compression and neurological deficit [ 1 , 15 ]. The lower cervical spine might undergo bone production, inflammation of the inter-apophyseal joints, and ossification of the anterior longitudinal ligament [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Up to 75% of axial PsA patients with longstanding disease have cervical spine damage involving C1-C2, where odontoid erosions and atlantoaxial instability can be found, leading to further complications, such as spinal cord compression and neurological deficit [ 1 , 15 ]. The lower cervical spine might undergo bone production, inflammation of the inter-apophyseal joints, and ossification of the anterior longitudinal ligament [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al’s study [ 21 ] showed that inflammatory changes in the spine and SIJ are less frequent compared to the high prevalence of back pain. At the same time, the axSpA and IBP criteria had poor sensitivity for MRI findings [ 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations